Tropisetron Preconditioning Decreases Myocardial Biomarkers in Patients Undergoing Heart Valve Replacement Surgery - Yu, Di; Gong, Xingrui; Zhang, Yufei; Li, Qing; Zhang, Mazhang (Frontiers in Medicine, 2022)
Background: Cardioplegic arrest during the heart valves replacement surgery frequently leads to myocardial damage. Tropisetron (TRP) has been demonstrated to reduce myocardial ischemia-reperfusion injury and inflammation in animals. We examined the efficacy of TRP in lowering myocardial biomarkers in patients undergoing heart valve replacement surgery. Methods: Seventy-five patients, scheduled for elective heart valve replacement surgery were randomly chosen to receive either 10 mL normal saline or 10 mg/10 mL TRP immediately after anesthesia induction. Blood samples for the measurement of cardiac troponin I (cTnI), creatine kinase (CK-MB), lactate dehydrogenase (LDH), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-10 (IL-10) were taken before anesthesia, as well as 4, 12 and 24 h after aortic cross-clamp release to evaluate myocardial injury using two-way ANOVA for repeated measurements. The study was registered at www.chictr.org.cn (number, ChiCTR-1800018681). Results: Treatment with TRP decreased the increment of cTnI at 12 and 24 h; of CK-MB at 4, 12, and 24 h; of TNF-α at 4 and 12 hours; and of LDH at 24 h after the release of the aortic cross-clamp. It increased IL-10 at 12 h after the release of the aortic cross-clamp. Multiple linear regression analysis showed that cardiopulmonary bypass (CPB) time was a risk factor, and that TRP treatment was a protective factor for postoperative cTNI change (β = 4.449, 95% CI [0.97-7.92], P = 0.013 for CPB time; and β = −381, 95% CI [−613.4 to −148.5], P = 0.002 for TRP treatment). Conclusions: TRP had cardioprotective and anti-inflammatory effects in patients undergoing heart valves replacement surgery with cardioplegic arrest. The addition of TRP and reduction of cardiopulmonary bypass time should be considered for myocardial protection in heart valve replacement surgery.